2022
DOI: 10.1002/pen.26050
|View full text |Cite
|
Sign up to set email alerts
|

Nanofiber‐Carbon black dual filler reinforced sustainable high‐performance Natural Rubber nanocomposites

Abstract: In the present work, uncured and cured properties of high-performance, sustainable Natural Rubber nanocomposites developed by leveraging the unique synergy between carbon black and fibrous nanofillers such as silicon carbide, carbon nanotubes, and aramid nanofibers were investigated. Reinforcement in these composites was analyzed using the properties of the unvulcanized compounds, which were then correlated with those of the vulcanized compounds. A 50% increment was recorded for the bound rubber content of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…1,2 Extrusion, as one of the common manufacturing methods, plays a vital role in rubber forming. [3][4][5] Nowadays, the automobile industry demands high-quality rubber products with complicated cross-sectional shapes, which presents new challenges to the current processing methods. The flow process of the compound melt in the runner is much more complex, and the design parameters of the runner and die are mostly empirically determined, with little guidance from theoretical calculations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Extrusion, as one of the common manufacturing methods, plays a vital role in rubber forming. [3][4][5] Nowadays, the automobile industry demands high-quality rubber products with complicated cross-sectional shapes, which presents new challenges to the current processing methods. The flow process of the compound melt in the runner is much more complex, and the design parameters of the runner and die are mostly empirically determined, with little guidance from theoretical calculations.…”
Section: Introductionmentioning
confidence: 99%
“…Because of its excellent vibration‐damping and sound‐insulating properties, rubber is widely used in the manufacture of tires, inner tubes, and sealing materials for windows, doors, and trucks 1,2 . Extrusion, as one of the common manufacturing methods, plays a vital role in rubber forming 3–5 . Nowadays, the automobile industry demands high‐quality rubber products with complicated cross‐sectional shapes, which presents new challenges to the current processing methods.…”
Section: Introductionmentioning
confidence: 99%
“…Due to these attributes, ANFs have been increasingly utilized as reinforcing organic nanofillers in polymer nanocomposites. [22][23][24][25][26][27][28] Patterson et al demonstrated that when ANFs are dispersed in the epoxy matrix of continuous macroscale aramid fiber (AF)-reinforced composites, they serve as effective reinforcement agents. This is achieved through improvements in both the matrix properties and modifications in the interfacial shear strength, thanks to hydrogen bonding and π-π interactions between the ANFs and macro AFs.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1–3 ] Excellent abrasion strength and improved processability are also reported by various research groups. [ 4,5 ] It must be kept in mind that such improvements come along with the challenges prevailing in handling these nanofillers and ensuring their exquisite dispersion in the matrix. [ 1,2 ] It is reported widely that the aspect ratio of nanofillers plays a noteworthy part in enhancing the reinforcing efficiency of nanofillers to develop polymer nanocomposites with better structural and functional performance.…”
Section: Introductionmentioning
confidence: 99%